2017
DOI: 10.1155/2017/4013685
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cytokine Profile in Relation to the Severity of Coronary Artery Disease

Abstract: Objectives. To investigate the potential association of a set of serum cytokines with the severity of coronary artery disease (CAD). Methods. A total of 201 patients who underwent coronary angiography for chest discomfort were enrolled. The concentrations of serum IFN-γ, TNF-α, IL-2, IL-4, IL-6, IL-10, IL-9, and IL-17 were determined by xMAP multiplex technology. The CAD severity was assessed by Gensini score (GS). Results. The serum levels of TNF-α, IL-6, IL-9, IL-10, and IL-17 were significantly higher in hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 30 publications
5
34
0
5
Order By: Relevance
“…A functional study found that the rs2275913 A allele is associated with a higher promoter activity of IL-17A, suggesting that the rs2275913 AA genotype appears to contribute to greater levels of inflammation, which can lead to several diseases, including CAD; this finding was consistent with the previous results showing that IL-17 may contribute to the severity of CAD. 21 For the IL-23R polymorphisms, we observed a borderline significant association between IL-23R rs6682925 and the risk of CAD that was consistent with the results of the previous study. 22 A functional study revealed that the rs6682925 C allele may increase the promoter activity of IL-23R.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A functional study found that the rs2275913 A allele is associated with a higher promoter activity of IL-17A, suggesting that the rs2275913 AA genotype appears to contribute to greater levels of inflammation, which can lead to several diseases, including CAD; this finding was consistent with the previous results showing that IL-17 may contribute to the severity of CAD. 21 For the IL-23R polymorphisms, we observed a borderline significant association between IL-23R rs6682925 and the risk of CAD that was consistent with the results of the previous study. 22 A functional study revealed that the rs6682925 C allele may increase the promoter activity of IL-23R.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, the significant association could not be maintained after the analysis was adjusted for the demographic characteristics of participants, indicating that the association between rs2275913 and CAD risk could be modified by patient characteristics. A functional study found that the rs2275913 A allele is associated with a higher promoter activity of IL‐17A , suggesting that the rs2275913 AA genotype appears to contribute to greater levels of inflammation, which can lead to several diseases, including CAD; this finding was consistent with the previous results showing that IL‐17 may contribute to the severity of CAD …”
Section: Discussionsupporting
confidence: 90%
“…Inflammation is both caused by and drives many chronic noncommunicable diseases, including COPD, atherosclerosis and T2D. Increased systemic inflammation has been reported in multimorbid patients when compared to those with a single disease or age-matched healthy volunteers [36,37]. It is important to note that while similar patterns of inflammation, including neutrophilic inflammation, are observed in COPD, atherosclerosis and T2D [38][39][40], inflammation is a mechanism that plays a role in numerous chronic and acute diseases.…”
Section: An Overview Of Mechanisms For Multimorbiditymentioning
confidence: 99%
“…24 Min et al found significantly raised serum IL-6 levels in coronary artery patients compared to healthy controls. 25 Ikonomidis et al observed raised serum IL-6 levels in a stable angina patients had more than twice median IL-6 (3.9 versus 1.7 pg/mL) compared to controls and found significant reduction in circulating IL-6 levels after aspirin supplementation in a randomized placebocontrolled trial. 26 Wainstein et al observed that serum IL-6 level above 1 pg/mL is predictive of significant CAD in 27% out of 48 patients with a mean 10-year and found to had 100% CAD.…”
Section: Discussionmentioning
confidence: 95%